2009
DOI: 10.4070/kcj.2009.39.9.367
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Natural History of Drug-Related Bradycardia

Abstract: Background and ObjectivesThe prognosis and natural history of bradycardia related to drugs such as beta-blockers and non-dihydropyridine calcium channel blockers are not well known.Subjects and MethodsWe retrospectively analyzed 38 consecutive patients (age 69±11, 21 women) with drug-related bradycardia (DRB) between March 2005 and September 2007. A drug-associated etiology for the bradycardia was established based on the medical history and patient response to drug discontinuation. The mean follow-up duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…Among the drug‐related bradycardias (DRBs), the BBs were the most common drugs (34%), and SAND was the major bradyarrhythmia (60%), especially in the patients receiving BBs and non‐DHP CCBs, which was consistent with recent studies on the incidence of DRBs (77–82% in SAND vs 18–23% in AVCD) 14,15 …”
Section: Discussionsupporting
confidence: 87%
“…Among the drug‐related bradycardias (DRBs), the BBs were the most common drugs (34%), and SAND was the major bradyarrhythmia (60%), especially in the patients receiving BBs and non‐DHP CCBs, which was consistent with recent studies on the incidence of DRBs (77–82% in SAND vs 18–23% in AVCD) 14,15 …”
Section: Discussionsupporting
confidence: 87%
“…In our study, we couldn't find any relationship between QRS duration or ventricular rate (as signs of supranodal or infra -nodal disease) [7][8][9] and AV block in drug users; in other word, ECG finding of supra or infra nodal block is not a predictor of permanent pacemaker requirement in patients who consumes drug and are on AV block. Another study that assessed the prognosis of bradycardia related to drugs, evaluated 38 patients with symptomatic bradycardia during beta blocker or calcium channel blocker consumption, and showed that in 10 of 38 cases, bradycardia were not caused by drugs, but were revealed by drugs [10]. Interestingly, in this study, if we omit cases with AV block from that 31 patients who came with symptomatic sinus bradycardia, 27(87%) patients with bradycardia will be resolved by discontinuation of drugs [10].…”
Section: Discussionmentioning
confidence: 99%
“…Another study that assessed the prognosis of bradycardia related to drugs, evaluated 38 patients with symptomatic bradycardia during beta blocker or calcium channel blocker consumption, and showed that in 10 of 38 cases, bradycardia were not caused by drugs, but were revealed by drugs [10]. Interestingly, in this study, if we omit cases with AV block from that 31 patients who came with symptomatic sinus bradycardia, 27(87%) patients with bradycardia will be resolved by discontinuation of drugs [10]. Comparing these studies, one can argue when a patient referred due to symptomatic bradycardia on beta blocker or calcium channel blockers, if the bradycardia is caused by the second or third degree AV block, it is less probably that the drug induces and if it is caused by sinus bradycardia it is most probably that the drug induces and will regress by discontinuation of drug.…”
Section: Discussionmentioning
confidence: 99%
“…Similar ECG diagnosis was reported in the above mentioned DRB study that sinus bradycardia and sinus bradycardia with junctional escape beats were most frequently observed. [35] Notably, our study did not report any in-hospital death as a result of symptomatic bradyarrhythmias. The contributing factors towards the irreversibility of bradyarrhythmias were beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 84%
“…Only 15% of patients who had second or third degree AV block during therapy with β-blockers, verapamil, or diltiazem was "truly caused by drugs". [34] A study by Lee, et al [35] found that β-blockers were the most common drugs associated with drug-related bradycardia (DRB). In this study, drug discontinuation was followed by resolution of bradycardia in 60% of patients.…”
Section: Discussionmentioning
confidence: 99%